THE ROLE OF FEEDBACK IN STUDENTS’ PROGRESS (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
Feedback plays a crucial role in helping students grow in their learning process and comprehension. Students get feedback in a variety of ways, such as from peers, teachers, and outside sources like employers or other sectors. In this paper, the role of feedback is discussed by elaborating on its dimensions, types, effectiveness, and the mechanisms through which it enhances student engagement and academic performance. The findings indicate that timely and constructive feedback fosters self-regulation, motivation, and enhanced academic results. Despite its significance, issues including differing student receptiveness and the requirement for teacher training in feedback delivery are highlighted. The research concludes that effective feedback is important for enhancing students' progress and should be implemented in educational practices.